An Analysis on Students' Anxiety in Writing Journal Article - Riza Nadia; Kadri Ramdani; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study is to investigate students' anxiety in writing journal article. A descriptive qualitative approach was employed, utilizing purposive sampling with 23 participants from Englis education students at universitas hamzanwadi. The data were collected through semi-structured interviews and focus group discussions. A prevalent theme that emerged from the data was the overwhelming pressure students feel to publish their research in academic journals. Participants expressed a sense of competition with peers and the need to meet institutional or departmental expectations for publication. This pressure often contributed to heightened levels of anxiety, as students feared the implications of not being able to publish their work. In conclusion, the analysis on students' anxiety in writing journal articles provides valuable insights into the emotional challenges faced by aspiring scholars during the publication process